1984
DOI: 10.1017/s0033291700015300
|View full text |Cite
|
Sign up to set email alerts
|

Sudden deaths in the mentally handicapped

Abstract: SynopsisTrends in the incidence and causes of sudden deaths in a hospital group for the mentally handicapped were identified during a 50-year period, and the two halves of the period were compared. There were significantly more deaths in the second 25-year period than in the first. Longevity was greater during the second period, and a decrease in deaths due to status epilepticus was outweighed by an increase in deaths from arterial degenerative disease in the larger number of older patients. In the second peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 12 publications
3
18
0
Order By: Relevance
“…Epilepsy has been described as not a common finding in Down syndrome and rarely documented as a cause of death in some studies, 23 contrasting with others who have found a high prevalence of epilepsy (8-17%) with an associated elevated mortality rate. 16 It appears that seizures occur in 5-7% of Down syndrome children, compared to 20-50% of children with other forms of mental impairment, but are found at a higher rate in adult Down syndrome individuals with dementia compared to those with Alzheimers disease in the general population.…”
Section: Central Nervous Systemmentioning
confidence: 80%
See 2 more Smart Citations
“…Epilepsy has been described as not a common finding in Down syndrome and rarely documented as a cause of death in some studies, 23 contrasting with others who have found a high prevalence of epilepsy (8-17%) with an associated elevated mortality rate. 16 It appears that seizures occur in 5-7% of Down syndrome children, compared to 20-50% of children with other forms of mental impairment, but are found at a higher rate in adult Down syndrome individuals with dementia compared to those with Alzheimers disease in the general population.…”
Section: Central Nervous Systemmentioning
confidence: 80%
“…Deep venous thromboses have been found in individuals with mental retardation who have not been mobilising, and fat embolism has been described following femoral fracture in older individuals. 23 Rarely, fatal coronary artery embolism with myocardial infarction may occur in Down syndrome. 24 …”
Section: Vascularmentioning
confidence: 99%
See 1 more Smart Citation
“…Several investigations (Beange et al 1995;Fisher 2004;Kerr et al 1996;Whitfield et al 1996) have suggested that the health mismanagement of this population has a severe impact on mortality Durvasula and Beange 2001;Hollins et al 1998); morbidity (Beange et al 1995;); and quality of life (Hensel et al 2002). Many of these medical conditions may cause the child with IDD pain, yet due to their inability to convey their pain and to present their suffering, they are doomed to experience delayed diagnosis and management of painful medical conditions, causing setbacks in hospitalization and even death (Carter and Jancar 1984;Mata 1960;Roy and Simon 1987).…”
Section: Health Status Of Children With Iddmentioning
confidence: 99%
“…The risk of asphyxiation will be increased if the person is noted to have cognitive impairment and oral stage dysfunction (Carter & Jancar 1984; Feinberg et al . 1992; Finestone et al .…”
Section: Introductionmentioning
confidence: 99%